Triple-Negative Essential Thrombocythemia: Clinical-Pathological and Molecular Features. A Single-Center Cohort Study - Cattaneo, Daniele; Croci, Giorgio Alberto; Bucelli, Cristina; Tabano, Silvia; Cannone, Marta Giulia; Gaudioso, Gabriella; Barbanti, Maria Chiara; Barbullushi, Kordelia; Bianchi, Paola; Fermo, Elisa; Fabris, Sonia; Baldini, Luca; et al. (Frontiers in Oncology, 2021)
Lack of demonstrable mutations affecting JAK2, CALR or MPL driver genes within the spectrum of BCR-ABL1-negative myeloproliferative neoplasms (MPNs) is currently referred to as triple-negative genotype, which is found in about 10% of patients with essential thrombocythemia (ET) and 5% to 10% of those with primary myelofibrosis (PMF). Very few papers are presently available on triple-negative ET, which is basically described as an indolent disease, differently from triple-negative PMF, which is an aggressive myeloid neoplasm, with a significantly higher risk of leukemic evolution. The aim of the present study was to evaluate the bone marrow morphology and the clinical-laboratory parameters of triple-negative ET patients, as well as to determine their molecular profile using next-generation sequencing (NGS) in order to identify any potential clonal biomarkers. We evaluated a single-center series of 40 triple-negative ET patients, being diagnosed according to the 2017 WHO classification criteria and regularly followed up at the Hematology Unit of our Institution, between January 1983 and January 2019. In all patients NGS was performed using the Illumina Ampliseq Myeloid Panel; morphological and immunohistochemical features of the bone marrow trephine biopsies were also thoroughly reviewed. Nucleotide variants were detected in 35 out of 40 patients. In detail, 29 subjects harbored one or two variants and six cases showed three or more concomitant nucleotide changes. The most frequent sequence variants involved TET2 gene (55.0%), followed by KIT (27.5%). Histologically, most of the cases displayed a classical ET morphology. Interestingly, prevalent megakaryocytes morphology was more frequently polymorphic with a mixture of giant megakaryocytes with hyperlobulated nuclei, normal and small sized maturing elements, and naked nuclei. Finally, in five cases a mild degree of reticulin fibrosis (MF-1) was evident together with an increase in the micro-vessel density. By means of NGS we were able to identify nucleotide variants in most cases, thus we suggest that a sizeable proportion of triple-negative ET patients do have a clonal disease. In analogy with driver genes-mutated MPNs, these observations may prevent the raise of issues concerning triple-negative ET treatment, especially when a cytoreductive therapy may be warranted.